Podoscypha ahuensis sp. nov. (Polyporales, Basidiomycota) evidenced by the morphological characters and phylogenetic analyses - Shen, Shan; Zhang, Cai-Wen; Zhang, Bao-Wei (Phytotaxa, 2024)
Using multiple lines of evidence, namely, morphological features and molecular evidence, we propose a new wood-inhabiting fungus, Podoscypha ahuensis. The species is characterized by its smooth, salmon to flesh pink or buff yellowish pileal surface, distinct swollen gloeocystidia, and the presence of pilocystidia and caulocystidia. Additionally, its basidiospores are ellipsoid and thin-walled (4.2–6.5 × 3–4.5 μm). We discovered this fungus on angiosperms in subtropical China. Sequences of the internal transcribed spacer (ITS) and the large subunit of nuclear ribosomal RNA (nLSU) gene regions of the studied samples were generated, and phylogenetic analyses were performed using the maximum likelihood, maximum parsimony, and Bayesian inference methods. Phylogenetic analyses based on the molecular data of ITS + nLSU sequences showed that P. ahuensis belonged to the Podoscypha, which, in turn, belongs to the family podoscyphaceae and is nested in the resudial clade. Further investigation was performed on more representative taxa in the Podoscypha based on ITS + nLSU sequences, the results of which demonstrated that the species P. ahuensis formed a monophyletic lineage with a strong support [99% BS, 1.00 BPP, 97% BP] and then grouped with P. brasiliensis and P. tropica.